Symbolic Data Analysis for the Assessment of User Satisfaction: An Application to Reading Rooms Services. - Sousa, Áurea (2014)
Special edition of the European Scientific Journal (ESJ): Conference proceedings: 1st Annual International Interdisciplinary Conference AIIC 2013, 24-26 April, Azores Islands, Portugal.